Trashumancia, Espacio para Poesía y Arte : mayo 92 - Ocaranza, Jorge Octavio (dirección); Gutiérrez Ramírez, Alfredo (dirección) (Trashumancia, 1992)
Contiene obra de: Alfredo Gutiérrez Ramírez, Alfredo R. Plascencia, Eugenio Partida, Bernardo Esquinca, Juan Hureña, Luis Armenta Malpica, Delenis Rodríguez, José Estanislao Cordero Serrant, Agustín Labrada Aguilera, Odette Alonso, Luis Medina, Alain Derbez, Alana Gómez, Carlos Rosas, Guadalupe Morfín, Herberto Helder, Jorge Orendain, Jaime Casillas, Silvia Eugenia Castillero y Martín Mora.